Optimal control involving sweeping processes with end point constraints - de Pinho, Maria do Rosário (2021)
We generalize a Maximum Principle, previously obtained, to cover optimal control problems involving sweeping processes and end point constraints. The work is based on an ingenious smooth approximating family of problems.